Synthesis and AChE Inhibitory Activity of Novel Thiazolylhydrazone Derivatives - Derya Osmaniye; Begüm Nurpelin Sağlık; Ulviye Acar Çevik; Serkan Levent; Betül Kaya Çavuşoğlu; Yusuf Özkay; Zafer Asım Kaplancıklı; Gülhan Turan (Molecules, 2019)
Alzheimer’s disease (AD) is the most common of the degenerative brain diseases and is described together with the impairment of cognitive function. Patients with AD lose the capability to code new memories, and life conditions are extremely difficult. The development of new drugs in this area continues at a great pace. A novel series of thiazole-piperazine hybrids, aimed against Alzheimer’s disease (AD), have been synthesized. The structure identification of synthesized compounds was elucidated by 1HNMR, 13C-NMR, and LCMSMS spectroscopic methods. The inhibitory potential of the synthesized compounds on cholinesterase enzymes was investigated. The compounds 3a, 3c and 3i showed significant inhibitory activity on the acetylcholinesterase (AChE) enzyme. On the other hand, none of the compounds showed significant inhibitory activity on the butyrylcholinesterase (BChE) enzyme. In addition to enzyme inhibition studies, enzyme kinetic studies were performed to observe the effects of the most active inhibitor compounds on the substrate−enzyme relationship. In addition to in vitro tests, docking studies also indicated that compound 3c potentially acts as a dual binding site AChE inhibitor.